Photodetachment of hydrogen negative ion inside a circular microcavity - 王德华 刘声 李绍晟 王一豪 (Chinese physics B, 2013)
The photodetachment of a hydrogen negative ion inside a circular microcavity is studied based on the semiclassical closed orbit theory. The closed orbit of the photo-detached electron in a circular microcavity is investigated and the photodetachment cross section of this system is calculated. The calculation result suggests that oscillating structure appears in the photodetachment cross section, which is caused by the interference effects of the returning electron waves with the outgoing waves traveling along the closed orbits. Besides, our study suggests that the photodetachment cross section of the negative ions depends on the laser polarization sensitively. In order to show the correspondence between the cross section and the closed orbits of the detached electron clearly, we calculate the Fourier transformation of the cross section and find that each peak corresponds to the length of one closed orbit. We hope that our results will be useful for understanding the photodetachment process of negative ions or the electron transport in a microcavity.